Clinical and morphological aspects of thin glomerular basement membrane disease - Żurawski, Jakub; Salwa-Żurawska, Wiesława; Woźniak, Aldona; Bortkiewicz, Elżbieta; Maciejewski, Janusz; Idasiak-Piechocka, Ilona; Urbański, Bartosz (Polish Journal of Pathology, 2009)
The report presents the results of investigations carried out in 63 patients (49 children and 14 adults) with thin glomerular basement membrane disease. Of 49 children, 13 came from nine families with family members suffering from kidney diseases (mostly manifested by haematuria). In the group of children, the most frequent initial clinical symptom (noted in 29 cases) was isolated haematuria, more rarely (in eight cases) haematuria and proteinuria, and (in seven cases) nephrotic syndrome. Isolated proteinuria was observed in another three children. In the adults, only in five patients was isolated haematuria the initial symptom of the disease; more frequently (in seven cases), they presented with isolated proteinuria. In two patients, proteinuria and haematuria were noted. In the two groups of patients, in addition to markers of thin glomerular basement membrane disease, the authors also observed markers indicative of other glomerulopathies: in seven children and four adults focal segmental glomerulosclerosis (FSGS) without any other glomerular pathologies (with the exception of thin glomerular basement membrane disease). Also in cases in which in addition to thin glomerular basement membrane disease other glomerular pathologies were present (mesangial hypercellularity, mesangial glomerulonephritis), matrix expansion was detected; this phenomenon might be considered a harbinger of glomerular sclerosis. In general, although not in each and every case, these pathologies were associated with duration of the disease.